2013
DOI: 10.1007/s10616-013-9584-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of spermatogonial stem cell-like cells from murine testicular tissue into haploid male germ cells in vitro

Abstract: In vitro differentiation of spermatogonial stem cells (SSCs) promotes the understanding of the mechanism of spermatogenesis. The purpose of this study was to isolate spermatogonial stem cell-like cells from murine testicular tissue, which then were induced into haploid germ cells by retinoic acid (RA). The spermatogonial stem cell-like cells were purified and enriched by a two-step plating method based on different adherence velocities of SSCs and somatic cells. Cell colonies were present after culture in M1-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It has been shown that mouse SYCP1 functions in synaptonemal complex assembly, meiotic recombination, and XY body formation . The expression of SYCP3 is related to the differentiation of the spermatogonial stem cells into haploid male germ cells . XRN2 is a 5′‐3′ exoribonuclease that is essential for embryogenesis, larval development, and fertility of C. elegance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that mouse SYCP1 functions in synaptonemal complex assembly, meiotic recombination, and XY body formation . The expression of SYCP3 is related to the differentiation of the spermatogonial stem cells into haploid male germ cells . XRN2 is a 5′‐3′ exoribonuclease that is essential for embryogenesis, larval development, and fertility of C. elegance .…”
Section: Discussionmentioning
confidence: 99%
“…37 The expression of SYCP3 is related to the differentiation of the spermatogonial stem cells into haploid male germ cells. 38 XRN2 is a 5′-3′ exoribonuclease that is essential for embryogenesis, larval development, and fertility of C. elegance. 39 Spermatid Perinuclear RNA Binding Protein (STRBP) is involved in spermatogenesis process and thus male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured at 37.1 °C under an atmosphere of 95% humidified air with 5% CO 2 . To induce differentiation, the cells were cultured in medium containing retinoic acid (Sigma Chemical Company, St. Louis, MO, USA) and other growth factors described in literature14. To examine the effect of IL-6, the cells were cultured in medium containing 0, 10, 50 and 100 ng/ml IL-6.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, different approaches have been proposed that could direct the differentiation of SSCs all the way to haploid male germ cells. Using isolated 6-day-old mouse SSCs, production of haploid germ cells was achieved by culturing testicular cells in 10% FBS-supplemented media for 3 days, changing the media into a retinoic acid (RA)-enriched medium to induce differentiation for 2 days, and followed by changing the media again to the first medium for 6-8 days [107].…”
Section: Two-dimensional Culture Of Testis Cell Suspensionsmentioning
confidence: 99%